2010
DOI: 10.1016/j.trstmh.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity to anti-phenolic glycolipid-I in leprosy cases, contacts and no known contacts of leprosy in an endemic and a non-endemic area in northeast Brazil

Abstract: The seroprevalence rates of IgM anti-phenolic glycolipid-I (PGL-I) antibodies in four study groups with differing exposure to Mycobacterium leprae in Ceará, Brazil were investigated between March 2005 and August 2006. The first three groups in a high prevalence area included 144 cases of leprosy, their 380 contacts and 317 participants with no known leprosy contact. The fourth group in a low prevalence area consisted of 87 participants with no known leprosy contact living in an area in which no cases of lepros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
14
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
6
14
0
3
Order By: Relevance
“…Although these studies found no differences in seropositivity rates among HHC of MB and paucibacillary leprosy (PB) lep-MB and paucibacillary leprosy (PB) lepand paucibacillary leprosy (PB) leppaucibacillary leprosy (PB) lepleprosy patients, our results indicated a slight difference in serum anti-PGL-1 IgM seropositivity rates between HHC of MB leprosy patients (56.8%) and of PB leprosy patients (43.1%), especially when comparing I leprosy patients (14%) x LL leprosy patients (29%) (p = 0.03). Similar results were reported by Calado et al (2005), Carbona-Castro et al (2008) and Frota et al (2010). The presence of serum antibodies suggests that the PGL-1 antigen induced a humoral immune response, but these increased antibody concentrations apparently could not block M. leprae multiplication in the host (Kaplan & Chase 1980, Touw et al 1982), as we found that two cases progressed to BT leprosy after one year of followup of these seropositive contacts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although these studies found no differences in seropositivity rates among HHC of MB and paucibacillary leprosy (PB) lep-MB and paucibacillary leprosy (PB) lepand paucibacillary leprosy (PB) leppaucibacillary leprosy (PB) lepleprosy patients, our results indicated a slight difference in serum anti-PGL-1 IgM seropositivity rates between HHC of MB leprosy patients (56.8%) and of PB leprosy patients (43.1%), especially when comparing I leprosy patients (14%) x LL leprosy patients (29%) (p = 0.03). Similar results were reported by Calado et al (2005), Carbona-Castro et al (2008) and Frota et al (2010). The presence of serum antibodies suggests that the PGL-1 antigen induced a humoral immune response, but these increased antibody concentrations apparently could not block M. leprae multiplication in the host (Kaplan & Chase 1980, Touw et al 1982), as we found that two cases progressed to BT leprosy after one year of followup of these seropositive contacts.…”
Section: Discussionsupporting
confidence: 91%
“…The phenolic glycolipid antibody (PGL-1), as measured using an enzyme-linked immunosorbent assay (ELISA), is considered to be a relevant marker of leprosy activity (Burgess et al 1988, Zenha et al 2009, Frota et al 2010). The PGL-1 fraction is part of the cell envelope of M. leprae and induces the production of the specific humoral response against PGL-1 detected in patient serum (Hunter et al 1982, Cho et al 1983, Foss et al 1993.…”
mentioning
confidence: 99%
“…The follow-up of these HC is of extreme importance, since an increase or maintenance of APGL-I levels indicates active subclinical infection (19) (20) (23) . Individual immunologic status could occult clinically detectable signs of leprosy for many years (24) .…”
Section: Discussionmentioning
confidence: 99%
“…The composition of antigens to include in such a test is not yet clear for leprosy. Rapid tests based solely on PGL-I derivatives have been developed and distributed but are not currently in widespread use and are somewhat restricted by high falsepositive rates within regions where leprosy is endemic and even in regions where it is not endemic (3,4,13,20). Our data indicate that while NDO-BSA can provide early diagnosis in armadillos, this can also be achieved with several protein antigens.…”
Section: Discussionmentioning
confidence: 99%